A sensitive detection of T4 polynucleotide kinase activity based on β-cyclodextrin polymer enhanced fluorescence combined with an exonuclease reaction. Issue 10 (18th December 2014) - Song, Chunxia; Yang, Xiaohai; Wang, Kemin; Wang, Qing; Liu, Jianbo; Huang, Jin; He, Leiliang; Liu, Pei; Qing, Zhihe; Liu, Wei
Abstract : A strategy for performing a polynucleotide kinase activity assay has been developed based on β-cyclodextrin polymer enhanced fluorescence combined with an exonuclease reaction. Abstract : A strategy for T4 polynucleotide kinase activity detection was proposed based on a β-cyclodextrin polymer (polyβ-CD) and an exonuclease reaction. The fluorescence of pyrene enhanced by more than 10 times in the presence of polyβ-CD, and a simple detection of T4 PNK was achieved with a detection limit of 0.02 units per mL.